2021
DOI: 10.1097/pap.0000000000000304
|View full text |Cite
|
Sign up to set email alerts
|

Mediastinal Germ Cell Tumors: A Review and Update on Pathologic, Clinical, and Molecular Features

Abstract: Mediastinal germ cell tumors (MGCTs) are the most common extragonadal germ cell tumors (GCTs) and most often arise in the anterior mediastinum with a male predilection. MGCTs also have a predilection for patients with Klinefelter syndrome and possibly other genetic conditions. MGCTs, as GCTs at other extragonadal sites, are thought to arise from germ cells improperly retained during migration along the midline during embryogenesis. Similar to their counterparts in the testes, MGCTs are classified into seminoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(56 citation statements)
references
References 148 publications
(375 reference statements)
0
56
0
Order By: Relevance
“…Laflamme et al reported that postpubertal PMNGCT had the poorer prognosis among GCTs, with a 5-year survival ratio of 45–50% ( 11 ). According to El-Zaatari et al ’s research ( 3 ), the median age at PMS onset was 33 years (range, 18 to 65 years) and the median age at PMNGCT onset was 28 years (range, 12 to 42 years). The occurrence of PMGCT showed a bimodal age distribution, with a first apex at 0–4 years of age, a decline in childhood, and then a second peak at 10–20 years of age.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Laflamme et al reported that postpubertal PMNGCT had the poorer prognosis among GCTs, with a 5-year survival ratio of 45–50% ( 11 ). According to El-Zaatari et al ’s research ( 3 ), the median age at PMS onset was 33 years (range, 18 to 65 years) and the median age at PMNGCT onset was 28 years (range, 12 to 42 years). The occurrence of PMGCT showed a bimodal age distribution, with a first apex at 0–4 years of age, a decline in childhood, and then a second peak at 10–20 years of age.…”
Section: Discussionmentioning
confidence: 98%
“…They are an uncommon group of tumors that account for just 2–5% of all GCTs. An increment of the short arm of chromosome (i12p) ( 3 ), which frequently results in the creation of an isochromosome, is a famous hallmark of malignant GCTs, both gonadal and extragonadal, and seminoma and non-seminoma. The primary mediastinal germ cell tumors (PMGCT) made up of non-seminomas and seminomas comprise 15% of adult mediastinal carcinomas ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…MYST is usually positive for LIN28, SALL4, Glypican-3, AFP, and PLZF, variable for keratins and CD117, but negative for OCT4, CD30, PLAP, Nanog, beta-hCG, and CD10. [60][61][62] Mediastinal embryonal carcinoma (MEC) usually occurs concurrently with other GCT components instead of pure MEC. 55 FNA of MEC component may show clusters of or single large highly atypical epithelioid cells with large round vesicular nuclei and prominent nucleoli (Fig.…”
Section: Mediastinal Germ Cell Tumorsmentioning
confidence: 99%
“…Mediastinal choriocarcinoma is extremely rare 60. FNA of mediastinal choriocarcinoma may show 2 populations of cells: syncytiotrophoblasts and cytotrophoblasts.…”
Section: Mediastinal Germ Cell Tumorsmentioning
confidence: 99%
“…Rarely, seminoma occurs outside of the gonads, with the mediastinum being the most common extragonadal location, because of defects from germ cell migration during embryogenesis. Mediastinal seminomas are indistinguishable from gonadal seminomas and are very sensitive to chemotherapy and radiation, as well as testicular seminomas [ 6 ]. Testicular seminoma is practically managed with surgical resection.…”
Section: Introductionmentioning
confidence: 99%